Common Contraceptive Shot May Increase HIV Risk. - Hamad, Lina Ashour Ali (faculty of Basic Medical Science - Libyan International Medical University, 2018)
This data were collected from three different studies(Hormonal Contraception and the Risk of HIV Acquisition: An Individual Participant Data Meta-analysis, Injectable birth control may raise HIV infection risk, and Depot-Medroxyprogesterone Acetate (DMPA) and HIV.) , all studies examining the association between use of injectable contraceptives comprising mostly DepotMedroxyprogesterone Acetate DMPA and the presence or acquisition of HIV. As a result there was an association between DMPA and increased risk of HIV acquisition according to several factors
In order for the HIV virus to be transmitted, there must be a point of access within the body where the infection may take place such as an open sore, a needle prick, a bleeding surface, inflammation or an otherwise fragile surface. Some studies suggest that the side effects associated with sex hormones that are used in hormonal birth control methods may increase the likelihood of these types of infection sites to occur. The hormones that are used in birth control pills can produce a variety of effects on the female reproductive system. Some explanations as to how this hormonal birth control method may increase the risk of HIV/AIDS transmission